2016
DOI: 10.1016/j.stem.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Apoptosis Overcomes Stage-Related Compatibility Barriers to Chimera Formation in Mouse Embryos

Abstract: Graphical Abstract Highlights d EpiSCs injected into blastocysts rapidly disappear due to apoptosis d Induced BCL2 expression enables injected EpiSCs to survive and form chimeras d BCL2-expressing Sox17 + endoderm progenitors can also form region-specific chimeras d BCL2-expressing rat EpiSCs form interspecies chimeras that survive to adulthood In Brief Masaki et al. show that expression of the anti-apoptotic gene BCL2 allows developmentally incompatible cells such as epiblast stem cells and endoderm progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 29 publications
2
99
1
2
Order By: Relevance
“…Indeed, forced expression of the apoptosis regulator BCL2 in mouse and rat EpiSCs allowed these cells to form chimeras when introduced into pre-implantation mouse blastocysts. Furthermore, not only EpiSCs, but also apoptosis-resistant endoderm progenitor cells, could form region-specific chimeras after transplantation into pre-implantation blastocysts (Masaki et al, 2016). If this system can also be applied to human cells, then it might prove possible to assess the developmental potency of cells by interspecies chimera assay.…”
Section: Chimera Generation By Apoptosis-resistant Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, forced expression of the apoptosis regulator BCL2 in mouse and rat EpiSCs allowed these cells to form chimeras when introduced into pre-implantation mouse blastocysts. Furthermore, not only EpiSCs, but also apoptosis-resistant endoderm progenitor cells, could form region-specific chimeras after transplantation into pre-implantation blastocysts (Masaki et al, 2016). If this system can also be applied to human cells, then it might prove possible to assess the developmental potency of cells by interspecies chimera assay.…”
Section: Chimera Generation By Apoptosis-resistant Cellsmentioning
confidence: 99%
“…The data from the Masaki et al (2016) study are intriguing for a number of reasons. First, they seem to hint at the existence of a mechanism that eliminates cells that are unmatched in terms of developmental stage by apoptosis.…”
Section: Chimera Generation By Apoptosis-resistant Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mashaki et al . revealed that E-CADHERIN (CDH1 ) and BCL2 play important roles in chimeric contribution by PSCs25. In this context, naïve-like CMK6 enhanced the expression of E-CADHERIN , but failed to express BCL2 (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…This migration causes the embryo to elongate, generating an asymmetrical elongated anterior to posterior epiblast (APE) (Degrelle et al, 2005; Lawson et al, 1991; Maddox-Hyttel et al, 2003). The epiblast in ERSE and APE stages remain pluripotent as suggested by clonal studies performed in the mouse (Lawson et al, 1991) and by chimera studies using mouse epiblast stem cells (mEpiSCs) (Huang et al, 2012; Masaki et al, 2016). Despite many conserved morphological features, the establishment of PSC cultures in vitro has proved challenging in species other than mouse and primates.…”
Section: Introductionmentioning
confidence: 99%